Dictionary of statistics and methodology - W Paul Vogt (Sage, 1993)
The book gives nontechnical definitions of a wide variety of statistical and methodological terms used in the social and behavioral sciences. Entries are in alphabetical order, the letter-by-letter (not word-by-word)method. In terms containing numbers, the numbers are spelled out and alphabetized accordingly. Greek letter are anglicized out, and alphabetized accordingly